2017
DOI: 10.1186/s13033-017-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depression among patients receiving treatment for snakebite in General Hospital, Kaltungo, Gombe State, Nigeria: August 2015

Abstract: BackgroundSnakebite though neglected, affects 5 million people yearly. More neglected is the psychological effect of envenomation. We determined prevalence and pattern of depression among patients admitted into snakebite wards of Kaltungo General Hospital Nigeria, and percentage recognized by clinicians. We also assessed for factors associated with depression.MethodsIn a descriptive hospital based study, we used Patient Health questionnaire (PHQ-9) to make diagnosis of depression among the patients. We reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The descriptions of these psychological consequences agree with previous studies in Sri Lanka [14,30] and Nigeria [15], which reported a variety of psychological outcomes secondary to snakebites, including anxiety, depression, and post-traumatic stress disorder. This issue deserves further investigations since it has been largely overlooked, not only in terms of research, but also in the lack of attention by public health systems.…”
Section: Physical and Psychological Sequelaesupporting
confidence: 89%
“…The descriptions of these psychological consequences agree with previous studies in Sri Lanka [14,30] and Nigeria [15], which reported a variety of psychological outcomes secondary to snakebites, including anxiety, depression, and post-traumatic stress disorder. This issue deserves further investigations since it has been largely overlooked, not only in terms of research, but also in the lack of attention by public health systems.…”
Section: Physical and Psychological Sequelaesupporting
confidence: 89%
“…These effects are unlikely to be direct venom effects, but rather the effects triggered by the traumatic experience of a snakebite and the severe socioeconomic consequences associated with snakebite. In a cross-sectional study done in Nigeria, depression was prevalent in 25% of 187 snakebite patients who were receiving treatment in the hospital [86]. The depression was associated with more severe complications in snakebite, being worried about family welfare, time and financial loss and previous experiences with snakebite.…”
Section: Psychological Effectsmentioning
confidence: 99%
“…Indeed we recently found all these factors are predictors of severe depression among victims of SB. 32…”
Section: Discussionmentioning
confidence: 99%